The political determinants of the health of undocumented immigrants: a comparative analysis of mortality patterns in Switzerland - Lorenzo Piccoli; Philippe Wanner (BMC, 2022)
Abstract Background The health of undocumented immigrants is an important concern in most societies. However, there is no conclusive evidence that inclusive health care policies lead to better outcomes for this group of the population. The aim of this study is to analyse whether there is an association between inclusive health care policies and the mortality patterns of undocumented immigrants, or the distribution of different causes of death among those who have died. Methods We analyse individual data concerning the deceased in Switzerland between 2011 and 2017. We proceed in two steps. First, we estimate and compare the patterns of mortality of Swiss citizens, documented immigrants, and undocumented immigrants. Second, we test whether there is an association between cantonal authorities' policies and differing mortality patterns. We use logistic regressions and multinomial regressions to estimate the relationship between legal status and mortality patterns both in Switzerland and across different cantons. Results We find a difference in the patterns of mortality between undocumented immigrants and the other groups of the population. Specifically, death from circulatory system diseases is twice as frequent among undocumented immigrants compared to documented immigrants and Swiss citizens. However, this difference is smaller in the Swiss cantons that have more inclusive health care policies towards undocumented immigrants. Conclusions We interpret these results as an indication that policies that expand access to health services lead to better outcomes for undocumented immigrants. This finding has implications for research on civic stratification and public health. Further analysis is needed to evaluate the effects of extending public health care for undocumented immigrants in different contexts.